Kupffer cell staining by an HFE-specific monoclonal antibody: implications for hereditary haemochromatosis. - Bastin, J; Jones, M; O'Callaghan, C; Schimanski, L; Mason, D; Townsend, A (1998)
Hereditary haemochromatosis is an inherited disorder of iron absorption that leads to excessive iron storage in the liver and other organs. A candidate disease gene HFE has been identified that encodes a novel MHC class I like protein. We report the development of a monoclonal antibody (HFE-JB1) specific for recombinant refolded HFE protein. The antibody immunoprecipitates a 49 kD protein from the cell line U937, a histiocytic lymphoma. It binds HFE but does not recognize other recombinant non-classic MHC class I proteins (HLA-E, F and G), nor does it react with a variety of recombinant classic class I MHC molecules. COS cells transfected with HFE in culture are stained specifically. The immunohistochemical staining pattern in human tissues is unique and can be defined as a subset of the transferrin receptor positive cells. In the liver HFE protein was shown to be present on Kupffer cells and endothelium (sinusoidal lining cells), but absent from the parenchyma. Kupffer cells from an untreated C282Y HH patient failed to stain with the antibody. In the normal gut scattered cells in the crypts are stained. HFE was also present on capillary endothelium in the brain (a site of high levels of transferrin receptor) and on scattered cells in the cerebellum and cortex. These results raise interesting questions concerning the function of HFE in the control of body iron content and distribution.